2015
DOI: 10.1080/09168451.2015.1050992
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of the resorcinomycin biosynthetic gene cluster

Abstract: Resorcinomycin (1) is composed of a nonproteinogenic amino acid, (S)-2-(3,5-dihydroxy-4-isopropylphenyl)-2-guanidinoacetic acid (2), and glycine. A biosynthetic gene cluster was identified in a genome database of Streptoverticillium roseoverticillatum by searching for orthologs of the genes responsible for biosynthesis of pheganomycin (3), which possesses a (2)-derivative at its N-terminus. The cluster contained a gene encoding an ATP-grasp-ligase (res5), which was suggested to catalyze the peptide bond format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The pheganomycins (PGMs, 125 – 129 ) were first isolated in the late 1980s from Streptomyces cirratus (Figure ). The amidinotides are hybrid NRPS/PKS-RiPP products owing to the presence of the nonproteinogenic ( S )-2-amino-2-(3,5-dihydroxy-phenyl)­acetic acid moiety. , An ATP-grasp ligase links a precursor peptide with this nonproteinogenic amino acid to yield the final product. Although the related compounds resorcinomycins A and B also possess the phenyl-2-guanidinoacetic acid moiety, they are not true RiPPs, as they contain a single Gly residue instead of a ribosomally synthesized peptide.…”
Section: Amidinotidesmentioning
confidence: 99%
“…The pheganomycins (PGMs, 125 – 129 ) were first isolated in the late 1980s from Streptomyces cirratus (Figure ). The amidinotides are hybrid NRPS/PKS-RiPP products owing to the presence of the nonproteinogenic ( S )-2-amino-2-(3,5-dihydroxy-phenyl)­acetic acid moiety. , An ATP-grasp ligase links a precursor peptide with this nonproteinogenic amino acid to yield the final product. Although the related compounds resorcinomycins A and B also possess the phenyl-2-guanidinoacetic acid moiety, they are not true RiPPs, as they contain a single Gly residue instead of a ribosomally synthesized peptide.…”
Section: Amidinotidesmentioning
confidence: 99%
“…As a first step, we examined the function of a PGM1 ortholog responsible for biosynthesis of resorcinomycin, which also has a phenyl glycine derivative (( S )-2-(3,5-dihydroxy-4-isopropylphenyl)-2-guanidinoacetic acid) at its N -terminus followed by glycine (Figure ). , Gene disruption of the PGM1 ortholog gene and heterologous expression of the gene cluster suggested that machinery similar to that of pheganomycin biosynthesis was utilized for resorcinomycin biosynthesis …”
mentioning
confidence: 99%
“…2,3 Gene disruption of the PGM1 ortholog gene and heterologous expression of the gene cluster suggested that machinery similar to that of pheganomycin biosynthesis was utilized for resorcinomycin biosynthesis. 4 In this study, we studied PGM1 orthologs found in actinobacteria, which constitute clusters of genes unrelated to pheganomycin and resorcinomycin biosynthesis. Because of the increasing availability of genome sequences, we identified many PGM1 orthologs in many different bacterial strains, mainly in actinobacteria.…”
mentioning
confidence: 99%
“…[20] Recently,Dairi and coworkers reported an amide bond formation by ATP-grasp enzymes in resorcinomycin and pheganomycin biogenesis. [21] Furthermore,wepostulate that the subsequent transfer of the b-lactone building block to the dipeptide might be catalyzed by the conserved putative AMP-dependent synthetases CysF and BelH.…”
Section: Communicationsmentioning
confidence: 99%